Does conjugation strategy matter? Cetuximab-conjugated gold nanocages for targeting triple-negative breast cancer cells. Issue 9 (6th August 2019) - Avvakumova, S.; Pandolfi, L.; Soprano, E.; Moretto, L.; Bellini, M.; Galbiati, E.; Rizzuto, M. A.; Colombo, M.; Allevi, R.; Corsi, F.; Sánchez Iglesias, A.; Prosperi, D.
Abstract : The efficient targeting of cancer cells depends on the success of obtaining the active targeting of overexpressed receptors. Abstract : The efficient targeting of cancer cells depends on the success of obtaining the active targeting of overexpressed receptors. A very accurate design of nanoconjugates should be done via the selection of the conjugation strategy to achieve effective targeted nanoconjugates. Here, we present a detailed study of cetuximab-conjugated nonspherical gold nanocages for the active targeting of triple-negative breast cancer cells, including MDA-MB-231 and MDA-MB-468. A few different general strategies were selected for monoclonal antibody conjugation to the nanoparticle surface. By varying the bioconjugation conditions, including antibody orientation or the presence of a polymeric spacer or recombinant protein biolinker, we demonstrate the importance of a rational design of nanoconjugates. A quantitative study of gold content via ICP-AES allowed us to compare the effectiveness of cellular uptake as a function of the conjugation strategy and confirmed the active nature of nanoparticle internalization in cancer cells via epidermal growth factor receptor recognition, corroborating the importance of the rational design of nanomaterials for nanomedicine.